2019
DOI: 10.1186/s12903-019-0912-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical parameters and oxidative stress markers in Tunisian patients with periodontal disease

Abstract: BackgroundOxidative stress is involved in many diseases including diabetes and cancer. Numbers of studies have suggested its involvement in the pathogenesis of periodontal diseases. The aim of this study was to evaluate the levels of biochemical parameters and oxidative stress markers in plasma of healthy and chronic periodontitis patients.MethodsOne hundred thirty subjects were divided into two groups; patients (mean age = 42 ± 13.6 y.o) and control (mean age = 44.8 ± 12.6 y.o). Patients and healthy subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 24 publications
2
26
0
2
Order By: Relevance
“…It was significantly decreased (P < 0.001) in the salivary and serum samples [Figures 1 and 3]. These results are in harmony with those recorded by Gharbi et al, 19 and Thomas et al, 20 In contrast, an article conducted by Panjamurthy et al 18 observed the high levels of catalase and SOD antioxidants in periodontitis. Glutathione is an example of thiol-containing peptides antioxidants.…”
Section: Conflicts Of Interestsupporting
confidence: 76%
“…It was significantly decreased (P < 0.001) in the salivary and serum samples [Figures 1 and 3]. These results are in harmony with those recorded by Gharbi et al, 19 and Thomas et al, 20 In contrast, an article conducted by Panjamurthy et al 18 observed the high levels of catalase and SOD antioxidants in periodontitis. Glutathione is an example of thiol-containing peptides antioxidants.…”
Section: Conflicts Of Interestsupporting
confidence: 76%
“…Lipid peroxidation degradation products such as malondialdehyde (MDA) and 4‐hydroxy‐2‐nonenal (4‐HNE) are detectable in biological fluids and indicate a pro‐oxidant state 6 . Increase in ROS levels cause oxidative stress 7 . Many salivary oxidative stress biomarkers can potentially be useful for screening of periodontal disease 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no clear explanation for the role of oxidative stress markers in the progression of periodontal diseases, studies are showing that the increase of oxidative stress products impairs periodontal regeneration or healing. Many studies have also reported that these oxidative stress products are associated with osteoclastic bone resorption and can induce the destruction of periodontal tissues (34). Besides, measuring oxidants individually is not only a practical method; but also it is a cheaper method to use the total oxidative status (TOS) and total antioxidant capacity (TAOC) measurement method (35).…”
Section: Discussionmentioning
confidence: 99%